Induction and Formation of Accessory Corpus Luteum After Artificial Insemination (AI) Might Increase Pregnancy Rate Per AI in Heat Stressed Dairy Cows - Stojanov Boris , Atanasov Branko , Grizelj Juraj , Vince Silvio , Nikolovski Martin , Kjosevski Miroslav, Dovenski Toni , Adamov Nikola , Ilievska Ksenija , Samardzija Marko (Faculty of Veterinary Medicine - Skopje, 2020)
The present study aimed to evaluate whether the induction and the formation of an accessory corpus luteum (CL) after AI might increase the pregnancy per AI (P/AI) in heat stressed dairy cows. Starting at d 50±3 post-partum, 113 lactating Holstein cows from one commercial herd during summer were scored for body condition, blood sampled and examined by ultrasound. Those bearing a CL>25mm and progesterone (P4) level>2ng/mL were synchronized using a double PGF2α injection given 12 h apart and AI-ed at detected estrus. In total 18 cows, there were not any signs of estrus (n=10) nor a P4 level <2ng/mL at the time of enrolment (n=8) and therefore they were excluded from the study, leading to 95 cows finally enrolled.. At d5 post-AI, cows were randomly allocated into 2 groups: control group (CON, n=45) without any additional treatment, and treatment group (GnRH, n=50), treated with 0.008 mg Buserelin – a GnRH agonist. Blood sampling and ultrasound examination were done at d5, d14 and at d21 after AI, whereas the pregnancy diagnosis was done at d21 and d30 after AI. Average daily temperature and relative humidity values were used to calculate the temperature-humidity index (THI). The average THI during the experiment was 79.5±0.6. At d5, no differences were observed neither between the number of the CL nor between the P4 level in both groups. At d14 and d21, 82% of the GnRH-treated cows had more than one CL versus 0% of the CON cows. Both at d14 and 21, GnRH-treated cows had higher P4 levels compared to the CON cows (p<0.05). In addition, P/AI were higher in the GnRH group than in the CON group (65% vs. 48.3%, p<0.05), whereas late embryonic losses were higher in CON in comparison to GnRH cows (10.6 vs. 4%, respectively). The BCS at the moment of insemination did not affect P/AI (p>0.05). In conclusion, the induction of an accessory CL at d 5 after AI might increase P/AI in heat stressed dairy cows.
Keywords: CL, AI, pregnancy rate, heat stress, cow